In Vitro Characterization of Sumoylation of HR Proteins - Altmannova, Veronika; Krejci, Lumir (Methods in molecular biology, 2021)
In vitro analysis of posttranslational modifications such as sumoylation provides a great tool to not only identify the target proteins but also to characterize the specific effects of this modification on the protein features and uncover possible regulatory mechanism. In this chapter, we will describe the purification of yeast SUMO machinery proteins and their use to identify SUMO modification of target proteins in vitro. Furthermore, we will show several examples characterizing the effect of sumoylation on the biochemical activities of various proteins involved in homologous recombination (HR) that helped to better understand the regulatory role of this modification.
Keywords: malé modifikační proteiny související s ubikvitinem; Homologous Recombination; Small Ubiquitin-Related Modifier Proteins; rekombinantní proteiny; Recombinant Proteins; homologní rekombinace; sumoylace; komplexy ubikvitinligas; Escherichia coli; Sumoylation; Escherichia coli Proteins; proteiny z Escherichia coli; Ubiquitin-Protein Ligase Complexes